Optimalisasi strategi konten Instagram untuk meningkatkan promosi jamu instan pada UMKM Snack Rahayu - Dean Subhan Saleh; Lintang Ayu Fathihatun; Euis Yuniarti; Ananda Putri Rahmah; Wahyu Yulianto (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
This mentoring program aims to support the use of Instagram as a promotional medium for instant herbal drink products at UMKM Snack Rahayu. Prior to the program, the business relied on door-to-door sales and had not used social media in a structured manner, resulting in limited market reach. The mentoring process included initial observation, problem identification, content concept development, and the creation and publication of initial trial content. During the program, three posts were published to assess audience responses and observe Instagram’s early promotional potential. The analysis indicates that simple content concepts and appropriate visual formats generated initial signs of increased interaction. Among the three posts published as initial trial content, video emerged as the most effective format, reinforcing that appropriate visual selection influences audience responses. The program also improved the owner’s understanding of posting consistency and visual coherence in building a basic digital identity, enabling the continued independent use of Instagram.